Effect of work schedule flexibility as a moderator in the relationship between job stress and wellbeing in pharmacy practice - Erum Rehman; Khalid Abdullah Alotaibi; Shazia Rehman; Mehmood Ahmad (Scientific Reports)
Abstract Hospital pharmacists frequently face significant job stress, adversely impacting their well-being. Work schedule flexibility is often proposed as a potential buffer against job stress, yet its effectiveness among hospital pharmacists remains understudied. This study investigates the moderating effect of work schedule flexibility on the relationship between job stress and well-being among hospital pharmacists in Punjab, Pakistan. A cross-sectional survey was conducted between September 2023 and January 2024, involving 414 pharmacists working in public hospitals in Punjab province. The study utilized standardized scales to measure well-being, stress levels, and work schedule flexibility among the participants. Bivariate correlation and multiple regression analyses examined the relationships and interaction effects among the study variables. Bivariate correlation analysis revealed a negative association between job stress and well-being, a positive association between work schedule flexibility and well-being, and a negative association between work schedule flexibility and job stress. Multiple regression analysis indicated that work schedule flexibility significantly moderated the relationship between job stress and well-being, with the interaction term showing a significant effect. The findings underscore the importance of work schedule flexibility in mitigating the negative effects of job stress on the well-being of hospital pharmacists. Implementing policies that enhance work schedule flexibility may serve as an effective strategy to improve pharmacists’ well-being and job satisfaction. Further research is needed to explore these dynamics in healthcare settings and among diverse professional groups.